SCAFFOLDING OF PROSPECTIVE MATHEMATICS TEACHERS ON FIELD EXPERIENCE PRACTICE AT QOMARUDDIN UNIVERSITY - Illah Winiati Triyana; Yeva Kurniawati (JURNAL EDUCATION AND DEVELOPMENT, 2024)
This study aims to determine the types of scaffolding strategies used by prospective mathematics teacher students and also the reasons for using these strategies. To achieve the purpose of this study, a research design with a concurrent embedded strategy of mixed methods approach was used with the research subject being students of semester VII of the Mathematics Education Study Programme at Qomaruddin University. The instruments used to collect data in this study were observation sheets and interview guidelines which had previously been declared valid by two experts. The results of data analysis showed that the type of scaffolding strategy most often used by research subjects was modelling the desired behaviour with a percentage of 39.35%, followed by the strategy of inviting student participation at 27.02%. Meanwhile, the strategies of offering explanations and verifying clarification of students' understanding were 16.13% each, and finally the least frequently used strategy was inviting students to provide instructions, which was 1.29%. Based on the results of the interview, the reasons for using the types of scaffolding strategies by prospective student teachers include that they want students to be able to understand the material provided simply and want to make students feel more relaxed and consider the teacher as a friend.